Psychocultural Correlates of Mental Health Service Utilization Among African American and European American Girls - Yasui, Miwa (Adm Policy Ment Health, 2015)
Structural equation modeling was used to examine the effects of cultural factors (ethnic identity, perceived discrimination), family relations, and child problem type on mental health service utilization in a community sample of 1,480 adolescent girls (860 African American, 620 European American) between ages 15 and 17 years enrolled in the Pittsburgh Girls Study. Results revealed ethnic identity, caregiver attachment, and conduct disorder were related to service use among African American girls. Among European American girls, correlate patterns differed by clinical need. Findings highlight the need for research on health disparities to examine racially specific influences on service utilization.